2010
DOI: 10.1007/s10753-010-9194-3
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Src-Suppressed C Kinase Substrate in Neuronal Death Caused by the Lipopolysaccharide-Induced Reactive Astrogliosis

Abstract: Src-suppressed C kinase substrate (SSeCKS), a protein kinase C substrate, is a major lipopolysaccharide (LPS) response protein, regulating the inflammatory process. In the process of spinal inflammatory diseases by LPS intraspinal injection, expression of SSeCKS in the spinal cord was increased, mainly in active astrocytes and neurons. Induced SSeCKS was colabeled with terminal deoxynucleotidyl transferase-mediated biotinylated-dUTP nick-end labeling (an apoptosis maker) in the late inflammation processes. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…In current study, we also showed that LPS induced astrocytes activation and up-regulated the expression of SSeCKS in astrocytes. These results are in agreement with our previous study (Shen et al 2009;Wang et al 2010). We consider that SSeCKS binds PKC in a phosphatidylserine-dependent manner and is also a major PKC substrate in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 94%
“…In current study, we also showed that LPS induced astrocytes activation and up-regulated the expression of SSeCKS in astrocytes. These results are in agreement with our previous study (Shen et al 2009;Wang et al 2010). We consider that SSeCKS binds PKC in a phosphatidylserine-dependent manner and is also a major PKC substrate in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 94%
“…Neuronal death/injury often leads to an increase of reactive astrocytes, a key event for brain inflammation [27]. We then examined glial fibrillary acidic protein (GFAP) marked reactive astrocytes in control and VPS35 CX3CR1 cortical brain in response to ischemia/stroke.…”
Section: Resultsmentioning
confidence: 99%
“…4F), suggesting that these enzymes are important signaling components in LPS-triggered inflammatory responses of macrophages. Indeed, the activation of these enzymes in many different inflammatory events triggered by LPS, poly(I:C), and peptidoglycan has been reported (Check et al, 2010;Wang et al, 2010).…”
Section: Resultsmentioning
confidence: 99%